Developing a Bilingual Storybook as English Reading Materials for Elementary School Students - Dian Sri Wahyuni; Tri Mulyati; indriani; Nur Muhammad Fathul Rozaq (LUNAR, 2026)
In the era globalisation, learning English is important in elementary school, one of which is reading English, because from reading they will gain information and knowledge. This research aim to develop and to know the feasibility level of bilingual storybook as an English reading materials. Apart from that, the reason for conducting this research is because there was a low reading level and there was no bilingual storybook based on local culture of Kemiren. The researcher used research and development (R&D) by Sugiyono. They are : (1) potential & problem, (2) data collection, (3) product design, (4) produk improvement, (6) product trials. The researcher cannot apply all ten stages because the research period was very limited. Bilingual storybook entitled “Jeje and Caca Go Around Kemiren” consist of two topics. They are : ritual traditions and traditional foods of Kemiren. Based on the validation results, the feasibility level of bilingual storybook get the average 88% from material expert and 95% from English teacher with very feasible category. While the evaluation results from small group trial get the average 100% from students with very feasible category. It can be concluded that bilingual storybook based on Kemiren local culture entitled “Jeje and Caca Go Around Kemiren” is suitable to use as English reading material.